A trend analysis of private label research between 2000 and 2012 - Molinillo-Jiménez, Sebastián; Ekinci, Yuksel; Whyatt, Georgina; Occhiocupo, Nicolettta (My University, 2014)
The aim of this study is to review the state of empirical and theoretical research about Private Label (PL) and to identify gaps and future research avenues. This paper uses a bibliometric approach of recent advances in the research of PL; it focuses on the period of greatest scientific output (2000-2012) and includes all international publications on PL in marketing journals ranked by the Academic Journal Quality Guide. The analysis systematically considers main authors and universities, countries, topics of investigation and methodologies used. The result reveals that research on the topic has been strongly influenced by a small group of authors and that most studies come from United States, Spain, United Kingdom, Netherlands, France, Australia and Germany. The paper discusses key emerging topics on PL such as consumer perceptions and behaviour, price, channel relationships and quality. Most of the articles have been focused on grocery products using a quantitative approach. Directions for future research are suggested.
Molinillo,S., Ekinci, Y., Whyatt, G., and Occhiocupo, N. (2014)'A Trend Analysis of Private Label Research Between 2000 and 2012'. in Gázquez-Abad, J.C., Martínez-López, F.J., Esteban-Millat, I. and Mondejar-Jiménez, J.A. (eds.) National Brand and Private Labels in Retailing. First International NB&PL, Barcelona, 25-27 June. Springer Proceedings in Business and Economics, pp. 171-178)
Keywords: Marcas registradas; Private label; Private brand; Store brand; Own-brand; Retail brand; Review